Kebijakan Pemerintah Daerah Dalam Pengelolaan Sumber Daya Alam Laut Di Wilayah Pesisir - Faiqah Nur Azizah (ADALAH, 2022)
The natural resources of the marine sector represent a key potential for Indonesia. This is because the marine area is wider than the land area. This potential can have a huge impact on the community because the town's dependence on marine potential is very strong. So that the economic activity of coastal communities continue to roll from time to time. However, in actuality, the potential of natural resources in the coastal area has so far not been optimized. So that it has an influence on coastal communities that are still battling with the difficulties of poverty and do not feel the beneficial impacts provided by the sea. The synergy between the central government and local governments in the management of natural resources in coastal areas is the key to accomplishing a national economic recovery in the marine resources sector.